The shining - King, Stephen, 1947- (New English Library ; Times Mirror, 1978)
"Danny is only five years old but in the words of old Mr Halloran he is a 'shiner', aglow with psychic voltage. When his father becomes caretaker of the Overlook Hotel his visions grew frighteningly out of control." -- p. [1].